The Sub Prime Crisis: Implications for Emerging Markets1 - Gwinner, William B.; Sanders, Anthony (International Journal of Property Sciences (E-ISSN: 2229-8568), 2009)
This paper discusses some of the key characteristics of the U.S. subprime mortgage boom and bust, contrasts them with characteristics of emerging mortgage markets, and makes recommendations for emerging market policy makers. The crisis has raised questions in the minds of many as to the wisdom of extending mortgage lending to low and moderate income households. It is important to note, however, that prior to the growth of subprime lending in the 1990s, U.S. mortgage markets already reached low and moderate -income households without taking large risks or suffering large losses. In contrast, in most emerging markets, mortgage finance is a luxury good, restricted to upper income households. As policy makers in emerging market seek to move lenders down market, they should adopt policies that include a variety of financing methods and should allow for rental or purchase as a function of the financial capacity of the household. Securitization remains a useful tool when developed in the context of well-aligned incentives and oversight. It is possible to extend mortgage lending down market without repeating the mistakes of the subprime boom and bust.